DEVELOPMENT STUDENT WORKSHEETS WITH PROBLEM-BASED LEARNING MODELS IN STATISTICS CLASS VIII MTs HIDAYATUL MUTA’ALLIM MENGKIRAU - Dewi Fitriyah; Rezi Ariawan; Zetriuslita; Hayatun Nufus (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
This study aims to determine the validity of the mathematics learning tools in the form of Student Worksheets (LKPD) using the Problem Based Learning (PBL) learning model on statistical material. This study uses a type of R&D research that was developed using the modified Plomp development model because the research was carried out during the Covid-19 pandemic, so only 4 stages were carried out, namely 1) the initial investigation stage, 2) the design stage, 3) the realization/construction stage, 4) stage of test, evaluation and revision. The data collection instrument used was the LKPD validation sheet. The data collection technique used is a non-test technique with validation sheets from 2 lecturers of mathematics education at FKIP UIR and 1 mathematics teacher at MTs Hidayatul Muta'allim Mengkirau. The analytical technique used is validation data analysis. From the results of the study, the results of the LKPD validation were 85.47% with very valid validation criteria. Based on this research, it was obtained a mathematics learning tool in the form of LKPD with a Problem Based Learning (PBL) model on statistical material for class VIII MTs Hidayatul Muta'allim Mengkirau which had been tested for validity.